2021
DOI: 10.1016/j.ejca.2021.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor seroconversion and adverse events to SARS-CoV-2 mRNA BNT162b2 vaccine in cancer patients on active treatment

Abstract: Purpose Initial findings in patients with cancer suggest a lower seroconversion to SARS-COV-2 vaccination possibly related to myelo-immunosuppressive therapies. We conducted a prospective study to assess factors predicting poor seroconversion and adverse events following immunization (AEFI) to the BNT162b2 vaccine in patients on active treatment. Patients and methods Cancer patients candidate to two doses of BNT162b2 SARS-COV-2 vaccination were enrolled. Patients on act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 31 publications
2
28
1
Order By: Relevance
“…Previous studies have shown that it can take 4-5 weeks to reach peak antibody responses following a primary infection ( 20 ), and this may even take months in those with severe disease ( 21 ). There are studies that describe older age as a predictor of poor seroconversion ( 22 ), perhaps due to potential comorbidities or immunosenescence. As such, it is possible that some of the 10 individuals that were seropositive during the first survey had antibody responses that remained on the rising phase and have yet to reach peak IgG levels by the time of the first survey.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that it can take 4-5 weeks to reach peak antibody responses following a primary infection ( 20 ), and this may even take months in those with severe disease ( 21 ). There are studies that describe older age as a predictor of poor seroconversion ( 22 ), perhaps due to potential comorbidities or immunosenescence. As such, it is possible that some of the 10 individuals that were seropositive during the first survey had antibody responses that remained on the rising phase and have yet to reach peak IgG levels by the time of the first survey.…”
Section: Discussionmentioning
confidence: 99%
“…Added to chemotherapy negative impact, some factors were found to be significantly associated with a lack of immunization ( 34 , 35 ): age, long-term corticosteroid treatment and lymphocyte count < 1 × 10 9 /L.…”
Section: Introductionmentioning
confidence: 99%
“…Both systemic and locoregional side-effects including fatigue, hypersensitivity reactions, fever, asthenia, vomiting, headaches, muscle and joint pain, chills, transient lymphadenopathy and injection site reactions (pain, erythema, itchiness, swelling, and redness) were reported. Although the various instruments and methods which were used for assessment of frequency, severity, and extend of the side-effects make it difficult to perform a meta-analysis investigation in this context, most of reported vaccines related side-effects were grade II, maximally ( 7 , 11 , 15 , 17 , 19 , 20 , 22 , 24 , 28 , 32 , 35 37 ).…”
Section: Discussionmentioning
confidence: 99%